MARKETING MIX, SATISFACTION & CUSTOMER LOYALTY NEW KUTA GREEN PARK PECATU BADUNG - Putu Hendita Melati Hapsari (Universitas Pendidikan Nasional, 2015)
The purpose of this study were 1) To analyze the effect of the level of quality of a productto customer satisfaction New Kuta Green Park Pecatu Badung. 2) To analyze the effect ofprices of products to customer satisfaction New Kuta Green Park Pecatu Badung. 3) Toanalyze the effect of the strategic location of the customer satisfaction New Kuta Green ParkPecatu Badung. 4) To analyze the effect of attractiveness of sale to the customer satisfactionNew Kuta Green Park Pecatu Badung. 5) To analyze the effect of service quality on customersatisfaction New Kuta Green Park Pecatu Badung. 6) To analyze the effect of the level ofcustomer satisfaction to customer loyalty New Kuta Green Park Pecatu Badung.The study found that 1) The best model obtained after modification is held, bycorrelating multiple error indicators that have modification index (MI) > 5,500. 2) structuralequation model modified otherwise good, because it has met the three criteria of eight cut ofvalue, namely criteria, Relative Chi-square, RMSA and TLI as well as three other criteriaclassified as marginal, Probability, GFI, and CFI. 3) From a structural equation showsRegression Weight (? ) seen there are five variables were significant positive effect, namely theinfluence of Product (X1) to Customer Satisfaction (Y), the influence of Place (X3) againstCustomer Satisfaction (Y), the influence Promotion (X4) to Customer Satisfaction (Y) and theinfluence of Provision of Customer Service (X5) against Customer Satisfaction (Y), and theeffect of Customer Satisfaction (Y) of the Customer Loyalty (Z). There is no significant negativeeffect Price (X2) against Customer Satisfaction (Y) 4) Influence on Customer Satisfaction (Y)is equal to 85.6%, and the influence on Customer Loyalty of 63.0%.Keyword : Product, Price, Place, Promotion, Provision of Customer Service, Customer Satisfaction and Customer Loyalty